Measuring Impulsive Buying Tendencies in Crotia: Towards Parsimonious Measurement Scale - Bošnjak, Michael (Array, 2007)
Departing from an English instrument proposed by Verplanken and Herabadi (2001), we propose a preliminary scale comprising eight items to parsimoniously measure impulsive buying tendencies in Croatia. The preliminary scale assesses two facets of impulsive buying tendencies, namely cognitive aspects (e.g. lack of planning and deliberation) as well as affective aspects (e.g., feeling of pleasure, excitement, compulsion, lack of control, regret). We describe the development steps involved, present data on the scales´ measurement model, and portray possible applications and avenues for future research.